An in vitro Evaluation of the Effect of Transient Electromagnetic Fields on Pacemakers and Clinical Mitigation Measures - Huang, Jing; Lin, Kaibin; Lu, Wu; Ding, Ranran; Wu, Bingjie; Cai, Mingqi; Nazarian, Saman; Zhao, Wenbin; Li, Jingbo; Huang, Dong (Frontiers in Cardiovascular Medicine, 2020)
Background The effect of transient electromagnetic fields on the function of pacemakers is not well evaluated. There is a lack of effective methods for clinicians to reduce electromagnetic susceptibility (EMS) during implantation of pacemakers. This study aimed to evaluate whether a novel method of handling the excess leads in the pocket can lower the EMS of pacemakers and consequently reduce the effect of electromagnetic interference caused by transient electromagnetic fields on pacemakers. Methods: An in vitro chest model was established to simulate the clinical condition of dual-chamber pacemaker implantation. Three different intertwining patterns of excess leads were examined: parallel, twisted once, and multiple twisted-pair. Oscillated currents were injected into a copper electrical wire set horizontally above the model to create a radiated magnetic field to simulate the transient daily electromagnetic exposure of pacemakers. The electromagnetic induction of current was measured. The occurrence of EMS-related adverse events was evaluated when the induced pulsed voltage was applied. Results: Transient electromagnetic fields can induce electromagnetic noise in the pacing loop and inhibit the release of pacing pulses. The multiple twisted-pair intertwining pattern of excess leads was associated with a lower induced voltage amplitude than both the parallel and once-twisted patterns (P＜0.001). Even once twisted could significantly reduce induced voltage amplitude compared to no twisted (P＜0.001). A lower incidence of pacing inhibition was also observed in the multiple twisted-pair group than in the other two groups (P＜0.001). Conclusions: Transient electromagnetic fields can cause pacing inhibition. Twisting the excess leads for multiple turns in the pocket is an effective method to reduce the EMS of the dual-chamber pacemaker.